Mexican-Origin Early Adolescents’ Ethnic Socialization, Ethnic Identity, and Psychosocial Functioning. - Umaña-Taylor, Adriana J.; O’Donnell, Megan; Knight, George P.; Roosa, Mark W.; Berkel, Cady; Nair, Rajni (Counseling Psychologist, 2014)
This study examined how parental ethnic socialization informed adolescents’ ethnic identity (EI) development and, in turn, youths’ psychosocial functioning (i.e., mental health, social competence, academic efficacy, externalizing behaviors) among 749 Mexican-origin families. In addition, school ethnic composition was examined as a moderator of these associations. Findings indicated that mothers’ and fathers’ ethnic socialization were significant longitudinal predictors of adolescents’ EI, although fathers’ ethnic socialization interacted significantly with youths’ school ethnic composition in fifth grade to influence EI in seventh grade. Furthermore, adolescents’ EI was significantly associated with increased academic self-efficacy and social competence, and decreased depressive symptoms and externalizing behaviors. Findings support theoretical predictions regarding the central role parents play in Mexican-origin adolescents’ normative developmental processes and adjustment and, importantly, underscore the need to consider variability that is introduced into these processes by features of the social context such as school ethnic composition.